PKM EDUCATION PREVENTION AND CONTROL OF COVID 19 IN CILOWONG VILLAGE TAKTAKAN SERANG CITY - Kusumawati, Nugrahini; Narmo, Maratik Jeremia; Dewi, Wulandari Riska; Qomara, Bagas Agung; Wahyuningsih, Novi (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2024)
Covid-19 is an acute respiratory disease caused by a new type of coronavirus. The disease first spread in Wuhan, China, spread almost all over the world, and caused a global pandemic. The main symptoms. The covid-19 disease includes cough, fever, and shortness of breath. This disease affects all groups, adults, the elderly, and children. Children need to get an easy-to-understand education about Covid-19 and its ways of prevention. This is the basis of the community service team to actively participate in efforts to prevent and control the Covid-19 virus by providing counseling or socialization about Covid-19 and its prevention efforts to the community. The purpose of this activity is so that the community gets socialization about the prevention of Covid-19 can understand the symptoms of Covid-19, how it is transmitted, and how to prevent it so that children can participate in efforts to prevent Covid-19 transmission starting from themselves.